An Analysis of Islamic Jurisprudence on the Marriage of Pregnant Women from the Perspective of Legal Validity in Islamic Law: Analisis Yurisprudensi Islam tentang Pernikahan Wanita Hamil dari Perspektif Keabsahan Hukum dalam Hukum Islam - Muhammadong (JSPH : Jurnal Sosial Politik Humaniora, 2026)
The paper discusses the perspectives of Islamic jurisprudence on the marriage of pregnant women in terms of their legitimacy in Islamic law. The problem is still relevant, as it continues to generate divergent understandings in society, notably concerning the legality of the marriage contract, the status of marital relations, and legal implications following marriage. This study employs normative method with library research strategy. Data were analysed from primary sources such as the Qur'an, hadith, and opinions of Islamic jurists and secondary sources such as books, journal articles, and pertinent Islamic legal literature. The peculiarity of this study is that it discusses systematically the marriage of pregnant women by combining the validity of contract, the legal legitimacy and family welfare in one analytical frame. The data indicate that there are different opinions in Islamic jurisprudence on this issue. Some scholars allow marriage under specific conditions, others are more restrictive with legal rules. The divergences stem from varying readings of the textual evidence, the status of pregnancy and the purpose of lineage protection. The study indicates that the validity of such marriage should be carefully evaluated in light of the Islamic legal sources, scholarly perspectives, and the notion of public interest.